Amiloride Clinical Trial In Optic Neuritis (ACTION) protocol: a randomised, double blind, placebo controlled trial. Issue 11 (9th November 2015) - McKee, Justin B; Elston, John; Evangelou, Nikos; Gerry, Stephen; Fugger, Lars; Kennard, Christopher; Kong, Yazhuo; Palace, Jacqueline; Craner, Matthew
Abstract : Introduction: Neurodegeneration is a widely accepted contributor to the development of long-term disability in multiple sclerosis (MS). While current therapies in MS predominantly target inflammation and reduce relapse rate they have been less effective at preventing long-term disability. The identification and evaluation of effective neuroprotective therapies within a trial paradigm are key unmet needs. Emerging evidence supports amiloride, a licenced diuretic, as a neuroprotective agent in MS through acid sensing ion channel blockade. Optic neuritis (ON) is a common manifestation of MS with correlates of inflammation and neurodegeneration measurable within the visual pathways. Amiloride Clinical Trial In Optic Neuritis (ACTION) will utilise a multimodal approach to assess the neuroprotective efficacy of amiloride in acute ON. Methods and analysis: 46 patients will be recruited within 28 days from onset of ON visual symptoms and randomised on a 1:1 basis to placebo or amiloride 10 mg daily. Double-blinded treatment groups will be balanced for age, sex and visual loss severity by a random-deterministic minimisation algorithm. The primary objective is to demonstrate that amiloride is neuroprotective in ON as assessed by scanning laser polarimetry of the peripapillary retinal nerve fibre layer (RNFL) thickness at 6 months in the affected eye compared to the unaffected eye at baseline. RNFL in combination with further retinal measures will also be assessed by optical coherence tomography. Secondary outcome measures on brain MRI will include cortical volume, diffusion-weighted imaging, resting state functional MRI, MR spectroscopy and magnetisation transfer ratio. In addition, high and low contrast visual acuity, visual fields, colour vision and electrophysiology will be assessed alongside quality of life measures. Ethics and dissemination: Ethical approval was given by the south central Oxford B research ethics committee (REC reference: 13/SC/0022). The findings from ACTION will be disseminated through peer-reviewed publications and at scientific conferences. Trial registration number: EudraCT2012-004980-39, ClinicalTrials.gov Identifier: NCT01802489 .